Investigating Business Drives : Intellectual Capital To Marketing Mix - Panjaitan, Roymon; Muhammad Iqbal Fassa; Deddy Sulaimawan; Dian Indriyani (Publisher Cv. Inara, 2021)
This paper examines the relation of intellectual capital relations in consumer behaviour with social media to the effectiveness of the marketing mix. Sampling as much as 98 responding with the type of sampling quota, data collection techniques with the questionnaire and interviews. The test coefficient of Path in PLS-SEM is used in this study to contribute data from the analysis of the path of consumer behaviour by using social media. Results found that variables of consumer behaviour and social media advertising have a significant effect on the marketing mix, whereas intellectual capital as a liaison variable is not significantly influenced by consumer behaviour and does not significantly affect the marketing mix. Total direct and indirect influence of consumer behaviour variables 54.4% and social media variables at 40.8% to the marketing mix